Bierens' and Johansen's method: Complements or substitutes? - Martin Wagner (Institute for Advanced Studies (IHS), 1999)
The paper compares the cointegration methods of Johansen and Bierens by means of simulations and a real world example. Drawing on the fact developed in a companion paper that the Johansen procedure has robustness properties against ARMA systems and the Bierens procedure is designed for ARMA systems a comparison between the two to find out in which cases the Bierens procedure outperforms the Johansen procedure seems to be reasonable exercise. It turns out that generally the Johansen procedure outperforms the Bierens procedure in terms of the quality of the tests as well as the approximation quality of the estimated cointegrating space to the true cointegrating space.
Keywords: C13; C15; C32; 330; cointegration; Johansen procedure; Bierens method; robustness; simulation; Hausdorff distance; Kointegration; Theorie